2020
DOI: 10.1101/2020.02.07.938472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subfield-specific Effects of Chronic Mild Unpredictable Stress on Hippocampal Astrocytes

Abstract: Major Depressive Disorder (MDD) is a debilitating neuropsychiatric illness affecting over 20% of the population worldwide. Despite its prevalence, our understanding of its pathophysiology is severely limited, thus hampering the development of novel therapeutic strategies. Recent advances have clearly established astrocytes as major players in the pathophysiology, and plausibly pathogenesis, of major depression. In particular, astrocyte density in the hippocampus is severely diminished in MDD patients and corre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…3 H). Previously, it has been shown that chronic mild unpredictable stress (CMUS) results in a significant increase in the branch width, albeit in the hilar astrocytes 27 . These results show that chronic DMI treatment and CMUS may have opposing effects on the thickness of astrocytic processes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 H). Previously, it has been shown that chronic mild unpredictable stress (CMUS) results in a significant increase in the branch width, albeit in the hilar astrocytes 27 . These results show that chronic DMI treatment and CMUS may have opposing effects on the thickness of astrocytic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli that influence the development or the onset or progression of neurodegenerative disorders robustly alter the morphology of neuronal and glial cells 18,20,42 . On the other hand, subtler changes in morphology can be induced by physiologically relevant stimuli [3][4][5]15,22,27,28 . In the comparison studies, SMorph took 40 seconds to complete the analysis and it was estimated to be 1080 times faster than the analysis in ImageJ, when the faster of the two Sholl analysis methods was considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations